Mental Development Of Preschool Children - B.A. Khodjayorova; S.F.Kipchakova (Academia One Publishing, 2024)
This article is about intellectual development of children of preschool age and organization of training them in modern teaching technology are urgent problems. It is planned to educate preschool children from their youth to love the Motherland, respect for adults, friendship, to feel beauty, and to make every child interested in knowledge
Keywords: intelligence; mental education; mental work; activity